Outcome of latissimus dorsi free flap in-case of large scalp defect a single center study - Islam, Abu Faisal M. Ariful; Ahmed, M. Iqbal; Uddin, M. Salah; Hamid, M. A. (International Surgery Journal, 2021)
Reconstruction of scalp and calvarial defects following trauma post burn and after tumor ablation frequently requires prosthetic cranioplasty and soft tissue coverage. Furthermore, patients often have advanced disease and receive perioperative radiotherapy following tumor ablation. We evaluated the outcome of scalp reconstruction in traumatic cases with a free Latissimus dorsi (LD) muscle flap in this setting. The aim of this study was to evaluate outcome of latissimus dorsi free flap in-case of large scalp defect. This prospective non-randomized study was conducted on 10 patients with scalp defects following trauma attended emergency unit and outpatient department of burn and plastic surgery, Dhaka medical college hospital (DMCH) in the period between July 2017 and June 2018. Durability of coverage, flap success, infection and overall satisfaction were studied. The age distribution of the study population shows highest number of patients (60%) were in middle (24-30 years) age group whereas lowest are in older group (30-50 years). The lowest age was 24 years and the highest age was 45 years. Highest number of patients (80%) were standard myocutanous type of flap whereas lowest were in (20.0%) were partial latissimus muscle flap. Outcome of the reconstruction (80.0%) were excellent 10% partial flap necrosis occur and total flap loss in 1 (10%) patient. The reconstruction of scalp defects continues to be a challenge for the reconstructive surgeon, who must achieve a satisfactory functional and aesthetic outcome.